Case studies in mental health in general practice: depression and malignancy. Issue 3 (1st September 2013) - Fehily, Sasha; Blashki, Grant; Judd, Fiona; Piterman, Leon; Yang, Hui
Abstract : We reported a case of a 58-year-old single mother, who was diagnosed with a grade 3 invasive ductal carcinoma with a total Nottingham score of eight. The patient is struggling with overwhelming thoughts about death, but denies suicidal ideation. There are many emotional difficulties a person must face on receiving a diagnosis of cancer. To provide appropriate medical treatment, it is crucial to differentiate these normal feelings from a mood disorder (major depression). Depression is more commonly associated with certain cancers, particularly oropharyngeal, pancreatic, breast, and lung cancers. Depression in individuals with cancer is linked to prolonged hospital stays, worse clinical outcomes, and a reduction in the quality of life. Strong evidence surrounds the benefits of psychotherapy in treating depression in patients with cancer. Pharmacologic therapy is indicated for individuals with moderate or severe depression.